Soil bacterial community characteristics and its effect on organic carbon under different fertilization treatments - Kong, Chenchen; Zhang, Shiwen; Yuan, Shengjun; Wang, Weirui; Song, Xiaoxin; Guo, Dandan; Lawi, Abubakar Sadiq (Frontiers in Microbiology, 2024)
By implementing small-scale and efficient fertilization techniques, it is possible to enhance the activity of microorganisms, thereby improving soil carbon sequestration and ecological value in agriculture. In this study, field experiments were conducted using various types of fertilizers: organic fertilizer, microbial fungal fertilizer, composite fertilizer, and an unfertilized control (CK). Additionally, different dosages of compound fertilizers were applied, including 0.5 times compound fertilizers, constant compound fertilizers, 1.5 times compound fertilizers and CK. Using advanced technologies such as Illumina MiSeq high-throughput sequencing, PICRUSt2 prediction, Anosim analysis, redundancy analysis, canonical correlation analysis, and correlation matrix, soil organic carbon (SOC) content and components, bacterial diversity, metabolic functions, and interaction mechanisms were examined in different fields. The results showed pronounced effects of various fertilization modes on SOC and the bacterial community, particularly in the topsoil layer (0–20 cm). Organic fertilizer treatments increased the richness and diversity of bacterial communities in the soil. However, conventional doses and excessive application of compound fertilizers reduced the diversity of soil bacterial communities and SOC content. Additionally, different fertilization treatments led to an increase in easily oxidizable organic carbon (EOC) contents. Interestingly, the relationship between SOC components and soil bacteria exhibited inconsistency. EOC was positively correlated with the bacterial diversity index. Additionally, Chloroflexi exhibited a negative correlation with both SOC and its components. The influence of metabolism on primary metabolic functions on the content of SOC components in the soil was more notable. It included seven types of tertiary functional metabolic pathways significantly correlated with SOC components (p < 0.05). These findings enhance the understanding of the relative abundance of bacterial communities, particularly those related to the carbon cycle, by adjusting agricultural fertilization patterns. This adjustment serves as a reference for enhancing carbon sinks and reducing emissions in agricultural soils.